Parents' Experiences With Ultrasound During Pregnancy With a Lethal Fetal Diagnosis - Erin M. Denney-Koelsch; Denise Côté-Arsenault; Erin Lemcke-Berno (SAGE Publishing, 2015)
This longitudinal naturalistic study sought to describe parent experiences of ultrasounds during pregnancies with lethal fetal diagnoses (LFDs). We interviewed 16 mothers and 14 partners twice during pregnancy and twice after birth and death of their infant. Parents reported that ultrasound providers had a profound impact on their experiences with LFDs. Within three stages of pregnancy (pre-diagnosis, learning the diagnosis, and living with the diagnosis), themes of optimistic expectation, hearing bad news, need to know , and time with baby emerged. The dynamics of interactions with ultrasound providers included differing goals and expectations , and compatibility of interactions . These interactions were either satisfying or added to parents' burden. Ultrasound providers have the opportunity to share valuable knowledge and facilitate understanding and precious time with the baby. Providers of obstetrical care can improve communication with parents with LFDs at critical time periods by matching their interaction to parents' needs.